All‐optical OOK‐TO‐QPSK modulation format conversion based on XPM. Issue 2 (February 2014) - Duarte, Vanessa C.; Shahpari, Ali; Drummond, Miguel V.; Teixeira, António; Nogueira, Rogério N.
ABSTRACT In this article, we propose and experimentally demonstrate all‐optical conversion of two nonreturn‐to‐zero on‐off‐keying signals at 10 and 20 Gb/s into 20 and 40 Gb/s quadrature phase shift keying signals. The presented modulation format converter relies on cross‐phase modulation in a highly nonlinear fiber. Simulation results are also presented, including the impact of amplitude‐to‐phase noise conversion, and show consistency with the experimental results. © 2014 Wiley Periodicals, Inc. Microwave Opt Technol Lett 56:355–359, 2014